Digital Literacy as a Tool for Countering Radicalism Among Islamic Boarding School Students (Santri) - Chotijah Fanaqi; An-Nisa Aina Nurwaidi; Ayu Sri Wahyuni (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
The use of digital media to spread extremism and radicalism is the driving force behind this research. This research aims to examine how the information literacy model counters radicalism narratives. A counter narrative is a narrative that is deliberately framed with the intention of countering or minimizing the influence of negative narratives that are intolerant and extreme (Wahid Foundation, 2021). This research method uses descriptive qualitative and verification testing to look at the information literacy model in counter narrative efforts carried out by four pesantren. Collective Data through interviews, FGDs, observations, and literature studies. Informants in this research include pesantren leaders and Santri representatives. The resource persons include the Head of the Garut Ministry of Religion Representative Office, the Head of the Garut National and Political Unity Office (Kesbangpol), the Garut MUI Board, and the Garut NU Fatayat Board. Result of this research showed that pesantren information literacy is effective in countering narratives of radicalism through interpretation to re-frame the meaning of jihad and da'wah that has been used as an argument by radical groups, strengthening national insight, pesantren entrepreneurship, and digital media literacy for santri. In solving the problem of radicalism, it is necessary to look at economic and religious factors. This is so the government can find the right reformulation to prevent radicalism and extremism. In addition, the role of women as the first school for children must be an important factor